Effects of Autologous Conditioned Serum, Autologous Protein Solution, and Triamcinolone on Inflammatory and Catabolic Gene Expression in Equine Cartilage and Synovial Explants Treated With IL-1β in Co-culture - Velloso Alvarez, Ana; Boone, Lindsey H.; Pondugula, Satyanarayana R.; Caldwell, Fred; Wooldridge, Anne A. (Frontiers in Veterinary Science, 2020)
Autologous conditioned serum (ACS) and autologous protein solution (APS) are newer therapeutic options for osteoarthritis (OA). Co-culture of cartilage and synovium stimulated with IL-1β produces a similar physiologic response to tissues from naturally-ocurring OA. The study objective was to investigate the effects of ACS, APS, and triamcinolone (TA) on inflammatory and catabolic gene expression of inflamed joint tissues in co-culture. Blood was collected and processed for ACS and APS from six horses. Cartilage and synovial explants were harvested from the stifle, placed in co-culture, and treated as: (1) unstimulated control (2) stimulated control (3) ACS at 25% v/v (4) ACS at 50% v/v (5) APS at 25% v/v (6) APS at 50% v/v, (7) TA (10-6 M). Treatment groups 2-7 were stimulated with IL-1β (10 ng/ml). Cultures were maintained for 96 hours, and then both media and explants were harvested for measurement of gene expression and protein. IL-1β stimulation significantly increased IL-1β (p = 0.029), IL-8 (p = 0.011) and MMP-3 (p = 0.043) expression in synovium and IL-1β (p = 0.003) and TNF-α (p = 0.001) expression in cartilage. Treatment with 50% ACS and APS v/v downregulated IL-1β expression in cartilage more than TA treatment (p = 0.001 and p =0.0004) and APS downregulated MMP-1 expression in synovial membrane (p = 0.025). Treatment with ACS and APS caused a trend in upregulation of IL-10 expression in synovium and type II collagen and aggrecan expression in cartilage. PGE2 media concentrations were significantly reduced following treatment with APS (13.7-fold decrease, p = 0.0001) and ACS (4.13-fold decrease, p = 0.024); while TA did not reduce PGE2 significantly (2.3-fold decreased p= 0.406). As disease-modifying therapies, ACS and APS modified the cellular response from synovial membrane and articular cartilage. ACS and APS may offer an improved strategy to improve clinical signs of horses with naturally occurring OA, compared to TA treatment.